EFFECTS OF AUDITORY AND VISUAL CUES ON GAIT IN A SUBJECT WITH PARKINSON DISEASE: A PILOT STUDY (Fiep Bulletin - online, 2013)
Parkinson's disease (DP) patients are attacked by many symptoms, mainly motors, that develops as time goes by, and, the disturbance on the gait gain a place of high light because progressively affects the mobility and independency of the PD patients. Many studies have been done using visual and auditory cues during the training of the gait, aiming to correct the alterations caused by PD, and in general it showing positives results, however, the studies analyzing the effects of the auditory and visual cues simultaneous are rare. In light of the need for further research established above, this study has as aim analyse the effects of auditory and visual cues on the gait patterns of PD patient. The subject recruited for this research descriptive of the type case study was a 76-year-old woman who had been diagnosed with PD 2 years ago. The subject completed walking trial in four different conditions: analyses of the gait with free speed without external cues (WC); analyses of the gait with audio cues (AC); analyse of the gait with visual cues (VC); analyses of the gait with audio and visual cues simultaneous (AVC). For the comparison among the different analyzed situations an ANOVA was applied (p? 0,05). Significant differences were verified (p
Keywords: gait; Parkinson's disease; sensorial cues